Destination Middle East : a handbook for Filipino women domestic workers - Alunan, Gina M.; Kanlungan Centre Foundation (Quezon City, Philippines). ([Quezon City] Kanlungan Centre Foundation, Inc., 1997)
Aims to provide ready-reference information regarding general issues and concerns of Filipino women domestic helpers. With statistics and simple black and white illustrations. Written in an easy-to-read style and is intented for the use of the general public.
"With the support of International Labour Organization"-- T.p.
Keywords: Women household employees -- Employment -- Middle East -- Handbooks, manuals, etc; Filipinos -- Employment -- Middle East -- Handbooks, manuals, etc; Filipino women household employees -- Middle East -- Handbooks, manuals, etc; Employment in foreign countries -- Handbooks, manuals, etc